Transforming Credit Guarantees in Indonesia: Legal Reform and Digital Innovation at Askrindo - Maulida, Aldehita Purnasanti; Angkasa, Angkasa; Suhadi, Suhadi; Munir, Abu Bakar (Journal of Law and Legal Reform, 2026)
Credit guarantee institutions play a pivotal role in expanding financial inclusion, particularly for Micro, Small, and Medium Enterprises (MSMEs), which contribute over 60% to Indonesia’s GDP and employ approximately 97% of the national workforce (Kemenkop UKM, 2024). PT Asuransi Kredit Indonesia (Askrindo), a state-owned enterprise under the Indonesia Financial Group (IFG), serves as a key factor in mitigating credit risk and facilitating access to financing through its guarantee schemes. This study critically examines the legal reform of credit guarantee mechanisms in Indonesia by analyzing the regulatory framework governing Askrindo and its ongoing digital transformation. The research highlights regulatory fragmentation across the Insurance Law (Law No. 40/2014), OJK regulations, and Ministry of Finance policies, which often results in operational inefficiencies and legal ambiguities in claim settlement and risk management. Concurrently, Askrindo’s digital initiatives—such as the implementation of e-guarantee platforms, AI-based credit scoring, and integration with national MSME databases—have significantly improved service delivery and data transparency. Empirical data from Askrindo’s annual reports (2020–2024) indicate an 18.7% increase in guaranteed credit volume following digital adoption, with a notable reduction in manual processing time by 42%. However, unresolved legal disputes related to 12.3% of defaulted claims underscore the urgency of harmonizing digital innovation with legal accountability. Interviews with regulators and Askrindo executives further reveal gaps in consumer protection, audit mechanisms, and legal clarity surrounding digital guarantees. Using a law and economics approach, this article argues that Indonesia’s credit guarantee system requires a comprehensive legal reform that aligns regulatory oversight with digital innovation. Important suggestions include creating a single set of laws for digital guarantees, requiring clear information sharing, and adding real-time audit trails to improve accountability and protect MSME beneficiaries.